Acute stress triggers sex-dependent rapid alterations in the human small intestine microbiota composition - Rodiño-Janeiro, Bruno K.; Khannous-Lleiffe, Olfat; Pigrau, Marc; Willis, Jesse R.; Salvo-Romero, Eloísa; Nieto, Adoración; Expósito, Elba; Fortea, Marina; Pardo-Camacho, Cristina; Albert-Bayo, Mercé; González-Castro, Ana María; Guagnozzi, Danila; et al. (Frontiers in Microbiology, 2025)
Background/aimsDigestive disorders of gut-brain interaction (DGBI) are very common, predominant in females, and usually associated with intestinal barrier dysfunction, dysbiosis, and stress. We previously found that females have increased susceptibility to intestinal barrier dysfunction in response to acute stress. However, whether this is associated with changes in the small bowel microbiota remains unknown. We have evaluated changes in the small intestinal microbiota in response to acute stress to better understand stress-induced intestinal barrier dysfunction.MethodsJejunal biopsies were obtained at baseline and 90 min after cold pain or sham stress. Autonomic (blood pressure and heart rate), hormonal (plasma cortisol and adrenocorticotropic hormone) and psychological (Subjective Stress Rating Scale) responses to cold pain and sham stress were monitored. Microbial DNA from the biopsies was analyzed using a 16S metabarcoding approach before and after cold pain stress and sham stress. Differences in diversity and relative abundance of microbial taxa were examined.ResultsCold pain stress was associated with a significant decrease in alpha diversity (P = 0.015), which was more pronounced in females, along with significant sex differences in the abundance of specific taxa and the overall microbiota composition. Microbiota alterations significantly correlated with changes in psychological responses, hormones, and gene expression in the intestinal mucosal. Cold pain stress was also associated with activation of autonomic, hormonal and psychological response, with no differences between sexes.ConclusionsAcute stress elicits rapid alterations in bacterial composition in the jejunum of healthy subjects and these changes are more pronounced in females. Our results may contribute to the understanding of female predominance in DGBI.